Literature Review: The Application of Information Technology in Enhancing Efficiency in Recruiting and Selecting Human Resources for Remote Work - Shah, Moh Ashraff; Choirunnisa , Zuyyina (Fakultas Ekonomi Universitas Kadiri, 2024)
This research investigates the evolving landscape of remote work recruitment in the era of globalization. Employing a qualitative approach through a literature review, the study highlights the complexity of the remote work recruitment process, necessitating tailored strategies in the digital age. Findings indicate that while the internet and social media may not significantly boost applicant quantity, they play a pivotal role in refining job openings' targeting, enhancing recruitment efficiency. The study recommends incorporating questionnaires and effective categorization methods in the selection process for increased accessibility and efficiency. Post-employment, the research suggests leveraging online work platforms for monitoring remote employee performance. This holistic approach ensures effective management, monitoring, and optimization of the remote workforce in the evolving remote work landscape.